Perforated peptic ulcer disease: mid-term outcome among Iranian population - Freshteh KAMANI; Mehrdad MOGHIMI; Seyed Ali MARASHI; Habibollah PEYROVI; Mehrdad SHEIKHVATAN (Turkish Journal of Gastroenterology, 2019)
-